2023
DOI: 10.1136/bmjopen-2023-073176
|View full text |Cite
|
Sign up to set email alerts
|

Exploring barriers to living donor kidney transplant for African, Caribbean and Black communities in the Greater Toronto Area, Ontario: a qualitative study protocol

Beth Edwards,
Lydia-Joi Marshall,
Ghazaleh Ahmadzadeh
et al.

Abstract: IntroductionLiving donor (LD) kidney transplant (KT) is the best treatment option for many patients with kidney failure as it improves quality of life and survival compared with dialysis and deceased donor KT. Unfortunately, LDKT is underused, especially among groups marginalised by race and ethnicity. African, Caribbean and Black (ACB) patients are 60%–70% less likely to receive LDKT in Canada compared with white patients. Research from the USA and the UK suggests that mistrust, cultural and generational norm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Other studies have also reported that African and Hispanic American patients were less willing to communicate their need for LDKT 43 , 71 compared to White participants. Our ongoing analysis of qualitative data collected from members of ACB, South Asian, and Chinese Canadian communities 24 suggest that this may be related to mistrust of the Canadian health care system, 72 , 73 gaps in transplant-related knowledge, 74 potential stigma associated with kidney failure, and cultural norms around privacy concerning health issues. 75 , 76 Patients may also have concerns about the impact of donation on the donor; therefore, they avoid talking about LDKT with their parents, children or other relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also reported that African and Hispanic American patients were less willing to communicate their need for LDKT 43 , 71 compared to White participants. Our ongoing analysis of qualitative data collected from members of ACB, South Asian, and Chinese Canadian communities 24 suggest that this may be related to mistrust of the Canadian health care system, 72 , 73 gaps in transplant-related knowledge, 74 potential stigma associated with kidney failure, and cultural norms around privacy concerning health issues. 75 , 76 Patients may also have concerns about the impact of donation on the donor; therefore, they avoid talking about LDKT with their parents, children or other relatives.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 , 17 Frequently, the term “race” is used to ascribe individuals to groups based on ancestral origin, which is assumed to contribute to genetic, cultural, educational, and socioeconomic characteristics of group members. Instead, we use the term “racialization” 18 , 19 , 20 , 21 , 22 , 23 , 24 to emphasize the complex historical, social, and political processes that form the racialized categories. This term also indicates that the processes forming and reinforcing those categories are, frequently and to a large extent, driven and informed by values, judgments, biases, and sociopolitical structures external to the affected individuals and groups.…”
mentioning
confidence: 99%